Curing composition, high temperature spalling resistant ultra-high performance concrete, and methods of making and using the same

CN123003170APending Publication Date: 2026-10-30CHINA RAILWAY CONSTRUCTION SCIENCE & TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611470019.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]然而,UHPC的极端致密性(渗透系数≤10-12m/s)在高温下反而成为其致命缺陷——内部水分在加热过程中快速汽化,蒸汽无法通过微孔(<10nm)逸散,导致内部压力急剧升高(>5MPa),最终引发爆裂剥落,严重威胁结构安全

Benefits of technology

[0030]本发明第四方面提供一种混凝土试件,包括上述提供的抗高温爆裂超高性能混凝土。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a curing composition, an anti-high-temperature-bursting ultra-high-performance concrete and a preparation method and application thereof, and the curing composition comprises protein fibers, and the protein fibers are decomposed by thermal denaturation in a temperature range of 150-300 DEG C. The curing composition can improve the pressure evolution and transmission behavior of the interior of the concrete under a heated state, so that the concrete can actively prevent burst and efficiently release pressure under a high-temperature environment, thereby improving the high-temperature safety of the ultra-high-performance concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of building materials technology, and in particular to a curing composition, high-temperature crack-resistant ultra-high performance concrete, its preparation method and application. Background Technology

[0002] Ultra-high performance concrete (UHPC) is widely used in bridges, high-rise buildings, marine engineering, and military protection due to its ultra-high strength, high density, and excellent durability. For example, in tunnel lining engineering, UHPC must withstand the impact of instantaneous high temperatures (300-600℃) caused by fire or explosion; the containment vessel of a nuclear power plant, as a protective barrier for the nuclear reactor, must withstand high-temperature steam pressure under accident conditions; the load-bearing columns of high-rise buildings must maintain structural stability during fires to prevent local collapse caused by high-temperature bursts; and petrochemical platforms and military bunkers must be exposed to complex environments such as high temperature and chemical corrosion for extended periods.

[0003] However, UHPC has extremely dense structure (permeability coefficient ≤10). -12 The high temperature (m / s) becomes its fatal flaw – the internal moisture vaporizes rapidly during the heating process, and the steam cannot escape through the micropores (<10nm), causing the internal pressure to rise sharply (>5MPa), eventually leading to bursting and spalling, which seriously threatens the structural safety.

[0004] While existing technologies attempt to improve high-temperature performance by introducing polymer fibers or lightweight aggregates, core issues remain, such as random pressure relief channels and a mismatch between steam generation and dissipation rates, making it difficult to meet the safety requirements of ultra-high performance concrete structures in high-temperature scenarios. Therefore, developing an ultra-high performance concrete that combines active crack prevention and efficient pressure relief has become a crucial issue that urgently needs to be addressed in this field. Summary of the Invention

[0005] This invention provides a curing composition that improves the pressure evolution and transmission behavior inside concrete under heated conditions, enabling the concrete to actively prevent cracking and efficiently relieve pressure in high-temperature environments, thereby enhancing the high-temperature safety of ultra-high performance concrete.

[0006] This invention provides an ultra-high performance concrete resistant to high-temperature cracking, which enables the material to form a stable steam conduction network at high temperatures, thereby achieving resistance to high-temperature cracking.

[0007] This invention provides a method for preparing high-temperature crack-resistant ultra-high performance concrete, which can be prepared efficiently through a simple process.

[0008] This invention provides a concrete specimen that can reduce the risk of localized steam pressure buildup, spalling, and cracking. Therefore, it is beneficial to improve the structural integrity, safety, and durability of tunnel linings, nuclear power plant protective structures, and load-bearing components of high-rise buildings in high-temperature service scenarios.

[0009] This invention provides a method for casting concrete specimens, which improves the structural integrity, safety, and high-temperature service reliability of concrete specimens under fire, explosion, or accidental temperature rise conditions.

[0010] The first aspect of the present invention provides a maintenance composition comprising protein fibers, wherein the protein fibers undergo thermal denaturation and decomposition within a temperature range of 150-300°C.

[0011] The maintenance composition described above, wherein the protein fibers have a weight-average molecular weight of 30-50 kDa, a fiber length of 6-12 mm, a linear density of 1.0-2.0 dtex, and a protein content of ≥80%; and / or,

[0012] The protein fiber is at least one selected from soybean protein fiber, corn protein fiber, wheat protein fiber, and silkworm pupa protein fiber; and / or,

[0013] This also includes porous active aggregates, with a 24-hour water absorption rate ≥15%, and an instantaneous water release rate at high temperatures that is more than 10 times higher than at room temperatures. The high-temperature zone ranges from 200-600℃, while the room-temperature zone ranges from 20-60℃; and / or,

[0014] It also includes water-reducing agents.

[0015] The maintenance composition as described above, wherein the porous active aggregate has a particle size range of 0.15-1.18 mm; and / or,

[0016] Porous active aggregates include macropores, where the pore size d1 satisfies 50 nm < d1 ≤ 500 nm; and / or,

[0017] Porous active aggregates also include mesopores, and the pore size d2 of the mesopores satisfies 2nm≤d2≤50nm.

[0018] The curing composition as described above, wherein the porous active aggregate is obtained by calcining and activating ceramsite at 500-800℃.

[0019] A second aspect of the present invention provides a high-performance concrete resistant to high-temperature cracking, comprising a concrete matrix material and the curing composition provided above.

[0020] The high-temperature crack-resistant ultra-high performance concrete described above comprises a concrete matrix material including calcium-containing cementitious materials and aggregates, wherein protein fibers are oriented in the calcium-containing cementitious materials with an orientation degree of 60%-80%.

[0021] The high-temperature-resistant, high-performance concrete described above comprises the following components in parts by weight:

[0022] The composition comprises 700-900 parts calcium-containing cementitious material, 80-200 parts porous active aggregate, 800-1000 parts aggregate, protein fiber, water-reducing agent, and water; wherein the volume fraction of the protein fiber relative to the calcium-containing cementitious material is 0.3-1.0%, and the volume fraction of the water-reducing agent relative to the total mass of the calcium-containing cementitious material is 1.8-3.0%; the mass ratio of water to the calcium-containing cementitious material is 0.16-0.20; and / or,

[0023] Calcium-containing cementitious materials include silicate cement and silica fume, with silica fume accounting for 15-25% by mass and the remainder being silicate cement.

[0024] A third aspect of this invention provides a method for preparing high-temperature crack-resistant ultra-high performance concrete, comprising the following steps:

[0025] The curing composition and the concrete matrix material are mixed and treated to obtain high-temperature crack-resistant ultra-high performance concrete.

[0026] The preparation method described above, wherein the mixing process includes the following steps:

[0027] Calcium-containing cementitious materials, aggregates, and water-saturated porous active aggregates are mixed and stirred at a frequency of 30-50Hz for 30-60 seconds; then water and water-reducing agent are added, and the mixture is stirred at a frequency of ≥50Hz for 2-3 minutes to form a paste; finally, protein fibers are added, and the mixture is stirred at a frequency of 30-50Hz for 2-4 minutes to obtain high-temperature resistant, high-performance concrete; and / or...

[0028] The protein fibers are first pre-dispersed and then mixed. The pre-dispersion process includes the following steps: the calcium-containing gelling material includes a first group of materials and a second group of materials. The protein fibers are pre-mixed with the first group of materials. The mass ratio of the first group of materials to the protein fibers is 10%-20%. The second group of materials is directly involved in the mixing process.

[0029] In the preparation method described above, the water-saturated porous active aggregate is obtained by water soaking pretreatment, which includes the following steps: soaking the porous active aggregate in water for ≥24h, and draining off the excess water until it is saturated and surface-dry.

[0030] A fourth aspect of the present invention provides a concrete specimen comprising the high-temperature crack-resistant ultra-high performance concrete provided above.

[0031] The fifth aspect of the present invention provides a method for casting concrete specimens, including the step of casting using the high-temperature crack-resistant ultra-high performance concrete provided above.

[0032] This invention provides a curing composition that incorporates protein fibers that undergo thermal denaturation and decomposition within a temperature range of 150-300°C. At room temperature, the protein fibers first establish interfacial bonds with the cement matrix through active groups such as amino, carboxyl, and hydroxyl groups, achieving a more uniform distribution through mixing and dispersion. Subsequently, at high temperature, the protein fibers undergo thermal denaturation and decomposition, forming interconnected microchannels in situ within the concrete. The interfacial embedding at room temperature determines the location, continuity, and connectivity of these microchannels, transforming the steam release process from random crack release to a more ordered internal flow. When concrete encounters fire or high-temperature environments, these interconnected microchannels significantly enhance the rate and order of steam release within the concrete, thereby achieving proactive anti-burst and high-efficiency pressure relief in fire or high-temperature environments, reducing the risk of high-temperature bursting and improving the high-temperature safety of ultra-high-performance concrete. Detailed Implementation

[0033] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0034] Ultra-high performance concrete (UHPC) is widely used in bridges, high-rise buildings, marine engineering, and military protection due to its ultra-high strength, high density, and excellent durability. However, the dense structure of UHPC also brings a serious problem—high-temperature cracking. When UHPC components are exposed to fire or high-temperature environments, the internal pore water vaporizes rapidly, and due to the extremely low permeability of the matrix (the permeability coefficient is usually below 10), the concrete cracks. -12 When the steam reaches a speed of m / s, it cannot dissipate in time, creating enormous pressure inside the material, ultimately leading to severe spalling of the surface concrete or even complete collapse. This bursting phenomenon often occurs in the early stages of a fire (approximately 200-300℃), posing a significant threat to structural safety.

[0035] To address the aforementioned defect of ultra-high performance concrete cracking when exposed to fire or high-temperature environments, the inventors analyzed methods for preventing high-temperature cracking of ultra-high performance concrete and found that existing technologies mainly adopt the following approaches:

[0036] One approach involves incorporating polymer fibers (such as polypropylene fibers and polyvinyl alcohol fibers) to create capillary channels through melting or decomposition at high temperatures, thereby releasing steam pressure. For example, patent CN115259793A discloses an ultra-high performance concrete and its preparation method for preventing high-temperature bursting. While blending polypropylene fibers with steel fibers and relying on fiber melting to form pressure-relief channels can suppress bursting to some extent, the interface stability between the polymer fibers and the cement matrix is ​​weak. Upon heating, the channels are prone to instability, making it difficult to sustain an orderly pressure-relief effect. Furthermore, the strength retention rate after high temperatures is low. Additionally, polypropylene fibers are non-polar materials, and their interfacial bonding with cement hydration products mainly relies on physical interlocking, lacking chemical bonding. The pores formed after high-temperature melting are isolated or semi-connected, resulting in low steam dissipation efficiency.

[0037] Secondly, lightweight porous aggregates are added to release moisture at high temperatures through the internal pores of the aggregates, thus alleviating steam pressure. For example, the relevant patent CN115572134B discloses a lightweight high-temperature resistant ultra-high performance concrete and its preparation method. By synergistically combining lightweight porous aggregates with inorganic high-temperature resistant components, it focuses on improving heat resistance and lightweighting. However, it does not achieve a precise match between the high-temperature steam generation rate and the escape channel, and still relies on passive pressure relief, resulting in insufficient anti-explosion stability.

[0038] More importantly, current technology has not found any reports of using protein fibers to improve the high-temperature cracking of UHPC. Protein fibers (such as soybean protein fiber and corn protein fiber) are rich in amino acids and polypeptide chains, and their molecular structure contains a large number of active groups such as amino (-NH2), carboxyl (-COOH), and hydroxyl (-OH). These active groups can undergo chemical adsorption and coordination reactions with cement hydration products, forming a stronger interfacial bond than polypropylene fibers. At the same time, when plant protein fibers undergo thermal denaturation and decomposition at high temperatures, they not only form physical microchannels, but their decomposition products (amino acids, polypeptide fragments) can also react with Ca in the cement matrix. 2+ A complexation reaction occurs, forming a dense calcium-organic composite layer on the channel wall, enhancing the channel's structural stability. This chemical interface enhancement mechanism is completely absent in synthetic polymer fibers such as polypropylene fibers.

[0039] Based on this, the present invention provides a maintenance composition comprising protein fibers, wherein the protein fibers undergo thermal denaturation and decomposition within a temperature range of 150-300°C.

[0040] Protein fibers first establish interfacial bonds with the cement matrix through active groups such as amino, carboxyl, and hydroxyl groups, achieving a more uniform distribution through mixing and dispersion. Subsequently, when the material is heated to 150-300℃, the protein fibers undergo thermal denaturation and decomposition, releasing microscale microchannels in situ for vapor migration. The connectivity coefficient of these microchannels can be as low as 0.58, and the channel spacing can be controlled within 50-150 μm. Compared to the 0.3 connectivity coefficient of channels formed after polypropylene fiber melting, the continuity of the vapor escape path in the concrete of this invention is significantly improved at high temperatures. Thus, the interfacial consolidation at room temperature determines the location and continuity of microchannel formation, while the thermal denaturation and decomposition at high temperature determines the timing of microchannel opening. These two processes are sequential in time and unfold around the same fiber trajectory in space, transforming the vapor escape process from random crack release to a more ordered internal flow release. This results in a more balanced internal pressure distribution of the material under high-temperature conditions, suppressing the risk of localized spalling and bursting, and balancing structural integrity at room temperature with response stability at high temperatures. Meanwhile, when protein fibers undergo thermal denaturation and decomposition at high temperatures, their decomposition products (amino acids, polypeptide fragments) can also react with Ca in the cement matrix. 2+ A complexation reaction occurs, forming a dense calcium-organic composite layer on the channel wall, which enhances the structural stability of the microchannel, enabling it to continuously exert an orderly pressure relief function, and it retains a higher strength after high temperature.

[0041] Based on the above analysis, it can be seen that in this application, by selecting protein fibers that undergo thermal response within the aforementioned temperature range, the fibers form interfacial embedding at room temperature and decompose into pores as needed at high temperature, thereby establishing a steam pressure relief channel with high continuity and structural stability. This can significantly improve the rate, order, and stability of steam escape from concrete, thereby achieving active anti-explosion and high-efficiency pressure relief of concrete in fire or high-temperature environments, reducing the risk of high-temperature explosion of concrete, and improving the high-temperature safety of ultra-high performance concrete.

[0042] Furthermore, protein fibers exhibit gradient thermal response pore-forming properties: at 150-200℃, the protein molecular chains of the fibers undergo thermal denaturation, intramolecular hydrogen bonds break, the fibers shrink longitudinally, and radial microcracks occur; at 200-250℃, the protein backbone breaks down into amino acids and polypeptide fragments, the fiber structure collapses, and microchannels with a diameter of 10-50 μm are formed; at 250-300℃, the amino acid fragments react with Ca in the cement matrix... 2+ A complexation reaction occurs, depositing a calcium-amino acid complex layer on the channel wall, which enhances the channel's high-temperature stability.

[0043] Furthermore, the protein fiber has a weight-average molecular weight of 30-50 kDa, a fiber length of 6-12 mm, a linear density of 1.0-2.0 dtex, and a protein content of ≥80%.

[0044] Protein fibers are produced by controlling the molecular weight to a range of 30kDa, 40kDa, 50kDa, or any combination thereof; the length to a range of 6mm, 8mm, 10mm, 12mm, or any combination thereof; the linear density to a range of 1.0dtex, 1.5dtex, 2.0dtex, or any combination thereof; and the protein content to be no less than 80%. This ensures that the protein fibers possess sufficient dispersibility and bridging ability during ultra-high performance concrete mixing, while also undergoing thermal denaturation and decomposition at 150-300℃ to form fine channels. This size and purity window reduces insufficient reinforcement due to excessively short fibers, agglomeration and entanglement due to excessively long fibers, and thermal instability caused by low protein content, thus achieving both room-temperature toughening and high-temperature pressure relief.

[0045] Furthermore, the protein fiber is at least one of soybean protein fiber, corn protein fiber, wheat protein fiber, and silkworm pupa protein fiber. Among them, plant protein fiber is easy to prepare on a large scale, while silkworm pupa protein fiber can provide an alternative source, and both can form microchannels that facilitate steam dissipation under heat.

[0046] Furthermore, it also includes porous active aggregates, which have a 24-hour water absorption rate of ≥15%, and an instantaneous water release rate in the high-temperature zone that is more than 10 times that in the normal-temperature zone. The temperature in the high-temperature zone is 200-600℃, and the temperature in the normal-temperature zone is 20-60℃.

[0047] The 24-hour water absorption rate of porous active aggregate is no less than 15%, indicating that it has sufficient internal water storage capacity. Porous active aggregate slowly releases water in the ambient temperature range of 20-60℃, providing a continuous "internal curing water source" for the hydration of cementitious materials, effectively inhibiting the auto-shrinkage and early cracking of UHPC, and improving volume stability. However, in the high-temperature range, the instantaneous water release rate reaches more than 10 times that in the ambient temperature range, indicating that it has a characteristic of rapid water release at high temperatures. The difference in water release rate between ambient and high temperatures stems from its hierarchical porous structure, which binds water through capillary action at low temperatures and allows it to escape rapidly due to the vaporization of free water at high temperatures. The rapid water release characteristic of porous active aggregate at high temperatures can synergize with the thermal response pore-forming characteristics of protein fibers, achieving a dynamic balance between vapor release rate and dissipation capacity. This further enhances the active anti-explosion response and high-efficiency pressure relief of concrete in fire or high-temperature environments, further reducing the risk of high-temperature cracking of concrete.

[0048] Furthermore, it also includes water-reducing agents. Water-reducing agents are used to reduce water consumption and improve slurry fluidity, so that protein fibers and porous active aggregates are evenly dispersed and local enrichment is avoided.

[0049] Furthermore, the water-reducing agent is a polycarboxylate-based high-efficiency water-reducing agent with a solid content of 35-45 wt% and a water reduction rate of 30-40%.

[0050] Furthermore, the particle size range of the porous active aggregate is 0.15-1.18 mm. Controlling the particle size of the porous active aggregate within the range of 0.15 mm, 0.5 mm, 0.8 mm, 1.18 mm, or any combination thereof, allows it to achieve better gradation compatibility and dispersion uniformity in the ultra-high performance concrete matrix. The aggregate is more likely to fully coat the paste during the mixing stage and form a stable internal pore network after hardening, thus taking into account construction fluidity, volume stability, and high-temperature response efficiency.

[0051] Furthermore, the porous active aggregate includes macropores with a pore size d1 satisfying 50nm < d1 ≤ 500nm, which can accommodate more free water and weakly bound water. When the temperature rises to the high-temperature zone, the macropores rapidly vaporize and form pressure relief channels, allowing the steam pressure to be released quickly, thereby improving the instantaneous steam exhaust capacity under conditions of 200-600℃.

[0052] Furthermore, the porous active aggregate also includes mesopores, the pore size d2 of which satisfies 2nm≤d2≤50nm. The mesopores can slowly adsorb and release moisture at room temperature to medium temperature by means of capillary action, continuously replenishing internal humidity, reducing self-drying shrinkage, and providing a controllable water source for subsequent heating.

[0053] By coordinating macropores and mesopores, with mesopores responsible for slow release and internal curing at room temperature and macropores for rapid release and pressure relief at high temperature, and in conjunction with the channels formed after the thermal denaturation and decomposition of protein fibers at 150-300℃, the system can perform water storage, water supply, and pressure relief functions at different temperature stages. This process achieves a temporal match between steam generation, migration, and dissipation, making ultra-high performance concrete less prone to sudden local pressure increases when heated. This ensures the integrity and crack resistance of the material under fire or accidental temperature rise, while also taking into account shrinkage control and improved durability at room temperature.

[0054] In one possible implementation, porous activated aggregate is obtained by calcining and activating ceramsite at 500-800℃. The pore network formed inside the calcined and activated ceramsite has open channels and hierarchical pore structure (macropores and mesopores), which can store moisture by capillary action at room temperature and continuously and slowly release it during the hydration process of concrete, playing an internal curing role and reducing the probability of autogenous shrinkage and early microcrack formation; at the same time, when the temperature rises to above 200℃, the free water in the pores rapidly vaporizes and is discharged through the open channels, which can provide a timely steam escape path at high temperature stages.

[0055] Furthermore, the expanded clay aggregate can be made from waste expanded clay aggregate, shale expanded clay aggregate, or fly ash expanded clay aggregate. By using industrial or natural waste resources such as waste expanded clay aggregate and shale for calcination and activation, solid waste resource utilization is achieved, significantly reducing the demand for high-carbon-emission cement and expensive nanomaterials, making it environmentally friendly.

[0056] A second aspect of the present invention provides a high-performance concrete resistant to high-temperature cracking, comprising a concrete matrix material and a curing composition.

[0057] By incorporating thermally decomposable protein fibers into the concrete matrix, ultra-high performance concrete can form a stable steam conduction network at high temperatures, thereby achieving resistance to high-temperature cracking.

[0058] Furthermore, the concrete matrix material includes calcium-containing cementitious materials and aggregates, with protein fibers oriented in the calcium-containing cementitious materials at an orientation degree of 60%-80%.

[0059] Protein fibers are not randomly distributed, but rather oriented along a preferred direction within the calcium-containing cementitious material during mixing, casting, and molding, aided by slurry flow shearing, staged stirring, or external field stimulation. This creates directional microchannels within the matrix. By controlling the orientation degree within a range of 60%, 70%, 80%, or any combination thereof, the protein fibers maintain good dispersibility while forming a sufficiently continuous directional interconnected structure. This is because the high directional consistency of the protein fibers within this range allows for earlier and more stable construction of vapor dissipation paths under high temperatures. This process achieves a synergistic balance between ordered pressure relief at high temperatures and structural integrity at room temperature, thereby suppressing localized spalling and cracking of ultra-high performance concrete during fires or abnormal temperature rises, ultimately improving the high-temperature safety and service reliability of the structure.

[0060] Furthermore, it includes the following components in parts by mass:

[0061] The composition includes 700-900 parts calcium-containing cementitious material, 80-200 parts porous active aggregate, and 800-1000 parts aggregate; the volumetric content of protein fiber relative to the calcium-containing cementitious material is 0.3-1.0%, and the volumetric content of water-reducing agent relative to the total mass of the calcium-containing cementitious material is 1.8-3.0%; it also includes water, with a mass ratio of water to calcium-containing cementitious material of 0.16-0.20.

[0062] During implementation, the volumetric content of protein fibers relative to calcium-containing cementitious materials is controlled within the range of 0.3%, 0.5%, 0.7%, 1.0%, or any combination thereof. This allows for the formation of sufficient interconnected channels upon heating without significantly weakening the strength at room temperature. The mass content of water-reducing agent is within the range of 1.8%, 2.0%, 2.5%, 3.0%, or any combination thereof. This helps maintain fluidity and inhibit protein fiber agglomeration under low water-cement ratio conditions. The mass ratio of water to calcium-containing cementitious materials is within the range of 0.16, 0.17, 0.18, 0.19, 0.20, or any combination thereof. This balances the water required for hydration with porosity control, thus achieving both early forming and high density.

[0063] Furthermore, the calcium-containing cementitious material includes silicate cement and silica fume, with silica fume accounting for 15-25% by mass and the remainder being silicate cement. This allows the slurry to maintain suitable fluidity for construction while forming a high-strength and high-density matrix, and provides a basis for the dispersion and interfacial bonding of the curing composition in the matrix.

[0064] Furthermore, the aggregate is at least one of quartz sand and manufactured sand.

[0065] Furthermore, the aggregate particle size is 0.15-0.6 mm.

[0066] Furthermore, the silicate cement is PII52.5 silicate cement with a specific surface area of ​​350-400 m² / kg.

[0067] Furthermore, the specific surface area of ​​silica fume is 18m². 2 / g, SiO2 content ≥92%.

[0068] Furthermore, silica fume can be replaced with mineral admixtures, which are made by ultra-fine grinding of slag and limestone powder, with a Dv90 of less than 10 μm.

[0069] A third aspect of this invention provides a method for preparing high-temperature resistant, high-performance concrete, comprising the following steps:

[0070] High-temperature crack-resistant ultra-high performance concrete is obtained by mixing the curing composition with the concrete matrix material. This high-performance concrete can be prepared efficiently through a simple process.

[0071] Furthermore, the mixing process includes the following steps:

[0072] Calcium-containing cementitious materials, aggregates, and water-saturated porous active aggregates are mixed and stirred at a frequency of 30-50Hz for 30-60 seconds; then water and water-reducing agent are added and stirred at a frequency of ≥50Hz for 2-3 minutes to form a slurry; finally, protein fibers are added and stirred at a frequency of 30-50Hz for 2-4 minutes to obtain high-temperature crack-resistant ultra-high performance concrete.

[0073] Calcium-containing cementitious materials, aggregates, and water-saturated porous active aggregates are first dry-mixed at low speed using variable frequency, controlled within a range of 30Hz, 40Hz, 50Hz, or any two of these frequencies, for 30 seconds, 40 seconds, 50 seconds, 60 seconds, or any two of these frequencies, to form a homogeneous initial mixture. Then, mixing water and a water-reducing agent are added, and stirring is continued at a higher frequency of at least 50Hz for 2-3 minutes to fully wet the cementitious materials and form a slurry with suitable fluidity. Finally, protein fibers are added, and stirring continues within a range of 30Hz, 40Hz, 50Hz, or any two of these frequencies for 2 minutes, 3 minutes, 4 minutes, or any two of these frequencies, to ensure uniform dispersion of the protein fibers in the matrix. This sequence allows the porous active aggregates to be pre-distributed before subsequent water addition to form a slurry, and the introduction of protein fibers during the slurry stage reduces fiber entanglement and agglomeration in the early dry stage. The fiber distribution is controlled by low-frequency stirring at 30-50Hz to ensure that its orientation degree is within the range of 60%-80%, and the channel spacing of the formed microchannels is controlled at 50-150μm to ensure the continuity of the vapor escape path.

[0074] Furthermore, the mixing process is carried out in a twin-shaft mixer.

[0075] Furthermore, the protein fibers are first pre-dispersed before being mixed. The pre-dispersion process includes the following steps: the calcium-containing gelling material includes a first group of materials and a second group of materials. The protein fibers are pre-mixed with the first group of materials. The mass ratio of the first group of materials to the protein fibers is 10%-20%. The second group of materials is directly involved in the mixing process.

[0076] Furthermore, the premixing process involves low-speed dry stirring for 1-2 minutes at a frequency of 30-40 Hz to ensure that the silica fume uniformly coats the fiber surface. The first material is silica fume, which, through its submicron-sized particle size and large specific surface area, effectively prevents protein fiber aggregation and improves dispersion uniformity.

[0077] By first contacting the protein fibers with a small amount of fine powder material to form a loose and dispersed state, and then incorporating them into the main mixing system, the fibers can be more easily wrapped by the slurry and spread evenly during subsequent high-frequency stirring, reducing local enrichment.

[0078] Furthermore, the water-saturated porous active aggregate is obtained through a water soaking pretreatment, which includes the following steps: soaking the porous active aggregate in water for ≥24 hours, and draining off excess water until it reaches a saturated surface-dry state. Specifically, this includes: soaking the porous active aggregate in water at a temperature of 20±5℃, with the water level at least 20mm above the aggregate surface, for ≥24 hours; repeatedly wiping the aggregate surface with a wrung-out damp towel until no excess water remains, or dehydrating it in a centrifuge at 1500r / min for 3-5 minutes until it reaches a saturated surface-dry state.

[0079] In this state, the porous active aggregate, after entering the concrete system, can gradually release moisture according to the pore size and temperature response under temperature rise conditions. Combined with the stable initial moisture content brought about by saturated surface dry control, the internal vapor migration process is more controllable. It also works synergistically with the protein fiber and water-reducing agent system in the curing composition to provide a continuous and uniform source of moisture for vapor dissipation in the high-temperature stage. As a result, the high-temperature crack-resistant ultra-high performance concrete produced subsequently has a more stable internal humidity distribution and more consistent high-temperature response characteristics.

[0080] A fourth aspect of the present invention provides a concrete specimen comprising the high-temperature crack-resistant ultra-high performance concrete provided above.

[0081] The concrete specimen was prepared using high-temperature-resistant ultra-high performance concrete, which maintains the high strength, high density, and load-bearing stability of ultra-high performance concrete at room temperature. When exposed to high-temperature environments, the internal components of the concrete can undergo structural regulation that facilitates vapor migration with temperature changes, thereby improving the orderly dissipation of internal vapor. Since the entire specimen is directly composed of high-temperature-resistant ultra-high performance concrete, the anti-burst mechanism at the material level can be fully reflected at the specimen level, thereby reducing the risk of local vapor pressure accumulation, spalling, and bursting. Therefore, it is beneficial to improve the structural integrity, safety, and durability of tunnel linings, nuclear power plant protective structures, and load-bearing components of high-rise buildings under high-temperature service scenarios.

[0082] The fifth aspect of the present invention provides a method for casting concrete specimens, including the step of casting with the high-temperature resistant and high-performance concrete provided above.

[0083] When the above-mentioned high-temperature crack-resistant ultra-high performance concrete is used for casting, protein fiber components with temperature response characteristics can be uniformly introduced into the mixture during the molding stage, thereby forming a stable and continuous functional distribution inside the specimen.

[0084] The present invention will be further described below through specific embodiments.

[0085] Example 1:

[0086] The preparation method of high-temperature crack-resistant ultra-high performance concrete in this embodiment includes the following steps:

[0087] (1) Prepare raw materials:

[0088] The raw materials consist of the following components in parts by weight:

[0089] 750 parts of calcium-containing cementitious material, 120 parts of porous active aggregate, and 900 parts of aggregate;

[0090] The volumetric content of protein fiber relative to calcium-containing cementitious materials is 0.5%, and the volumetric content of water-reducing agent relative to the total mass of calcium-containing cementitious materials is 2.4%.

[0091] It also includes water, with a mass ratio of water to calcium-containing cementitious material of 0.18.

[0092] Specifically: 600 kg / m³ of cement 3 Silica fume 150kg / m 3 Porous active aggregate 120kg / m 3 900kg / m³ of quartz sand 3 Polycarboxylate superplasticizer 18kg / m 3 Soybean protein fiber (0.5% by volume relative to calcium-containing gelling materials), water 135 kg / m³ 3 .

[0093] in:

[0094] Cement: P·II52.5 Portland cement, specific surface area 380m² 2 / kg.

[0095] Silica fume: specific surface area 18m³ 2 / g, SiO2 content ≥92%.

[0096] Porous activated aggregate: Ceramsite made from waste shale through calcination and activation at 650℃, with a particle size of 0.3-1.0mm and a water absorption rate of 18% in 24 hours.

[0097] Quartz sand: particle size 0.15-0.6mm.

[0098] Soybean protein fiber, 8mm in length, 1.5dtex linear density, and approximately 1.32g / cm³ fiber density, corresponding to a mass content of approximately 0.46% of the cementitious material mass.

[0099] Polycarboxylate superplasticizer: solid content 40%, water reduction rate 35%.

[0100] Water: The porous active aggregate carries approximately 21.6 kg of pre-absorbed water, and the actual amount of water added is 113.4 kg.

[0101] (2) Mixing and preparation:

[0102] Soak the porous active aggregate in water for 24 hours until it is saturated and surface-dry for later use.

[0103] A portion of silica fume was taken from the calcium-containing cementitious material of the raw materials as the first group of materials. The first group of materials was premixed and stirred with soybean protein fiber to make the fiber surface evenly coated with silica fume. The mass ratio of the first group of materials to soybean protein fiber was 15%, and the remaining calcium-containing cementitious material was the second group of materials.

[0104] The second set of materials, quartz sand, and water-saturated porous active aggregates were put into a twin-shaft mixer and dry-mixed at 45Hz for 45 seconds.

[0105] Add water and polycarboxylate superplasticizer, and wet mix at 55 Hz for 2.5 minutes;

[0106] Add pre-dispersed soybean protein fiber and stir at 35Hz for 3 minutes to obtain high-performance concrete resistant to high-temperature cracking.

[0107] Example 2:

[0108] The method for preparing high-temperature crack-resistant ultra-high performance concrete in this embodiment differs from that in Example 1 in that the calcium-containing cementitious material in the raw materials includes 500 kg / m³ of cement. 3 250kg / m³ of ultrafine mineral admixture 3 The ultrafine mineral admixture is made by ultrafine grinding of slag and limestone powder, with Dv90 < 10 μm.

[0109] Example 3:

[0110] The method for preparing high-temperature crack-resistant ultra-high performance concrete in this embodiment differs from that in Example 1 in that the raw materials include the following components in parts by mass:

[0111] 700 parts of calcium-containing cementitious material, 80 parts of porous active aggregate, and 800 parts of aggregate;

[0112] The calcium-containing cementitious material includes 560 parts of cement and 140 parts of silica fume.

[0113] The volumetric content of protein fiber relative to calcium-containing cementitious material is 0.3%, and the mass content of water-reducing agent relative to calcium-containing cementitious material system is 1.8%; the mass ratio of water to calcium-containing cementitious material is 0.16.

[0114] Example 4:

[0115] The method for preparing high-temperature crack-resistant ultra-high performance concrete in this embodiment differs from that in Example 1 in that the raw materials include the following components in parts by mass:

[0116] 900 parts of calcium-containing cementitious material, 200 parts of porous active aggregate, and 1000 parts of aggregate;

[0117] The calcium-containing cementitious material includes 675 parts cement and 225 parts silica fume.

[0118] The volumetric content of protein fiber relative to calcium-containing cementitious material is 1.0%, and the mass content of water-reducing agent relative to calcium-containing cementitious material system is 3.0%; the mass ratio of water to calcium-containing cementitious material is 0.20.

[0119] Example 5:

[0120] The method for preparing high-temperature crack-resistant ultra-high performance concrete in this embodiment differs from that in Embodiment 1 in that the equal volumetric admixture of soybean protein fiber is replaced with wheat protein fiber.

[0121] Example 6:

[0122] The method for preparing high-temperature crack-resistant ultra-high performance concrete in this embodiment differs from that in Embodiment 1 in that the equal volumetric admixture of soybean protein fiber is replaced with corn protein fiber.

[0123] Example 7:

[0124] The method for preparing high-temperature crack-resistant ultra-high performance concrete in this embodiment differs from that in Embodiment 1 in that the equal volumetric admixture of soybean protein fiber is replaced with silkworm pupa protein fiber.

[0125] Example 8:

[0126] The method for preparing high-temperature crack-resistant ultra-high performance concrete in this embodiment differs from that in Example 1 in that the volumetric content of soybean protein fiber relative to calcium-containing cementitious materials is 1.2%.

[0127] Example 9:

[0128] The method for preparing high-temperature crack-resistant ultra-high performance concrete in this embodiment differs from that in Example 1 in that porous active aggregate is replaced with an equal amount of quartz sand.

[0129] Example 10:

[0130] The preparation method of the high-temperature crack-resistant ultra-high performance concrete in this embodiment differs from that in Example 1 in that the porous active aggregate is not soaked in water but directly added to the mixing process.

[0131] Example 11:

[0132] The method for preparing high-temperature crack-resistant ultra-high performance concrete in this embodiment differs from that in Embodiment 1 in that porous active aggregate is replaced with waste ceramsite in equal amounts.

[0133] Comparative Example 1:

[0134] The preparation method of the high-temperature crack-resistant ultra-high performance concrete in this comparative example differs from that in Example 1 in that soybean protein fiber is replaced with an equal amount of polypropylene fiber.

[0135] Comparative Example 2:

[0136] The preparation method of the high-temperature crack-resistant ultra-high performance concrete in this comparative example differs from that in Example 1 in that: no soybean protein fiber is added, and the amount of porous active aggregate remains unchanged.

[0137] Experimental example:

[0138] 1. Structural characteristics characterization:

[0139] (1) Verification of the temporal synergistic effect of protein fibers and porous active aggregates: The high-temperature crack-resistant ultra-high performance concrete of Example 1 and Comparative Example 2 were made into concrete specimens, and samples were taken at different temperature nodes (150℃, 200℃, 250℃, 300℃, 350℃) to observe the changes in internal structure, as follows:

[0140] a. Water release rate of porous aggregate: The water release rate of the porous aggregate in Example 1 was determined using the isothermal weight loss method. The method is as follows: A porous reactive aggregate sample (accurately weighed 10.0 g) that had absorbed water to a saturated surface-dry state was placed in an oven preheated to a set temperature. The sample was removed and weighed after 0.5 h, 1 h, 2 h, and 4 h of heat treatment, and the mass change was recorded. The water release rate (g / g·h) = water loss per unit time / initial mass of the sample. The experiment was repeated 3 times and the average value was taken. The results are shown in Table 1.

[0141] b. Fiber state: Concrete specimens of the high-temperature crack-resistant ultra-high performance concrete of Example 1 and Comparative Example 2 were prepared by quenching sampling + SEM observation. The concrete specimens were placed in a high-temperature furnace and heated to the target temperature at a set heating rate. Then, they were quickly taken out and quenched in liquid nitrogen to terminate the thermal reaction process. Thin sheet samples were taken from the inside of the specimens. After epoxy resin potting, grinding, polishing and gold sputtering, the fiber morphology was observed by scanning electron microscopy (SEM) to determine the state of the fibers (intact dispersion / thermal deformation shrinkage / microcrack formation / main chain breakage and microchannel connection / channel wall composite layer formation). The observation results of Example 1 are shown in Table 1 and the observation results of Comparative Example 2 are shown in Table 2.

[0142] c. Internal Steam Pressure: A miniature pressure sensor was embedded in the center of the concrete specimen during casting (e.g., PT124G-121 type, range 0-10MPa, temperature resistance ≥600℃). The sensor lead was sealed from the side of the specimen. During the heating process, internal pressure data was continuously collected in real time using a data acquisition system, with a sampling frequency of 1 time / 10s. The steam pressure at each temperature node was taken as the stable average value during the isothermal phase at that temperature. The test results of Example 1 are shown in Table 1, and the test results of Comparative Example 2 are shown in Table 2.

[0143] d. Appearance: Visual grading method. After heating and natural cooling to room temperature, the appearance of the specimens was visually observed and graded. The grading criteria were: normal (no visible change), slight color change, slight bulging, network cracks, surface peeling, and severe cracking. The peeling depth and mass loss rate were measured simultaneously to aid in the evaluation. The observation results of Example 1 are shown in Table 1, and the observation results of Comparative Example 2 are shown in Table 2.

[0144] Table 1:

[0145]

[0146] Table 2:

[0147]

[0148] As shown in Table 1-2, within the critical bursting range of 200-300℃, the steam pressure of Example 1 remained below 3MPa (the critical bursting value is approximately 3-5MPa), while Comparative Example 2 exceeded the critical value at 250℃. This demonstrates that the timely formation of microchannels in plant protein fibers (200-250℃) and the synergistic effect of the vigorous water release from porous aggregates (above 200℃) are key to preventing bursting.

[0149] (2) Orientation: The high-temperature crack-resistant ultra-high performance concrete of Examples 1-11 was made into concrete specimens and cured according to standard for 28 days. Thin sections of the internal cross-section were cut perpendicular to the pouring flow direction. After grinding and gold sputtering, images were collected by randomly selecting no less than 10 fields of view at 50-200x magnification using a scanning electron microscope (SEM). The angle between the long axis of the visible protein fiber cross-section and the flow direction of the slurry (i.e., the main pouring / flow direction) in each field of view was statistically measured. The orientation was calculated using the formula: Orientation = (Number of fibers with an angle within ±30° / Total number of fibers) × 100%. The test results are shown in Table 3.

[0150] (3) Microchannel connectivity coefficient: The microchannel connectivity coefficient of the concrete specimens in Examples 1-11 was detected using three-dimensional micro-CT reconstruction method, as follows: High-resolution micro-CT (e.g., resolution ≤ 2 μm) was used to scan the high-temperature treated concrete samples to obtain three-dimensional volume data; the connected pore space was identified by threshold segmentation, and the ratio of the connected pore volume to the total pore volume was calculated, which is the connectivity coefficient. The detection results are shown in Table 3.

[0151] (4) Channel spacing: The nearest neighbor method was used to detect the microchannel spacing of the concrete specimens in Examples 1-11. Specifically, on the SEM cross-sectional image, the distance from the center of each identified fiber microchannel to the center of the nearest neighbor channel was measured. The distance values ​​of no less than 100 channel samples were counted, and the average value was taken as the channel spacing. The detection results are shown in Table 3.

[0152] Table 3:

[0153]

[0154] As shown in Table 3, the orientation degree of Examples 1-7 and Examples 9-11 is within the range set by this invention. The orientation degree of Example 8 (fiber content exceeds the range) drops to 52%, indicating that when the protein fiber content exceeds the range of this invention, it will affect the fiber orientation degree. The microchannel connectivity coefficient and channel spacing of Examples 1-11 are both within the range set by this invention, but the connectivity coefficient of Example 8 is also significantly lower than that of Example 1. Among them, Example 1 is the optimal ratio, with an orientation degree of 72%, a connectivity coefficient of 0.72, and a channel spacing of approximately 90 μm. This shows that by controlling the protein fiber content and porous active aggregate parameters within the range of this invention, a vapor dissipation channel network with ordered orientation, high connectivity, and uniform spacing can be obtained, thereby ensuring high-temperature pressure relief efficiency.

[0155] 2. Performance Testing:

[0156] (1) 28d compressive strength test: According to the compressive strength test method recorded in GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the high-temperature crack-resistant ultra-high performance concrete of Examples 1-11 and Comparative Examples 1-2 were made into concrete specimens, cured under standard conditions for 28 days, and then tested. The test results are shown in Table 4.

[0157] (2) 28-day flexural strength test: According to the flexural strength test method recorded in GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", a four-point bending loading method was adopted: the specimen size was a prism of 40mm×40mm×160mm, the support span was 120mm, the loading point spacing was 40mm (three-point loading), and the loading rate was 0.05-0.1mm / min; the flexural strength was calculated according to the formula f=FL / bh², where F is the failure load, L is the support span, b is the specimen width, and h is the specimen height. The high-temperature burst-resistant ultra-high performance concrete of Examples 1-11 and Comparative Examples 1-2 were made into concrete specimens, cured under standard conditions for 28 days, and then tested. The test results are shown in Table 4.

[0158] (3) 28d drying shrinkage rate test: According to the contact method of the test method in GB / T 50082 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", concrete specimens of the high-temperature cracking resistant ultra-high performance concrete of Examples 1-11 and Comparative Examples 1-2 were made into concrete specimens and cured under standard conditions for 28 days. The test results are shown in Table 4.

[0159] (4) High temperature bursting test: The high temperature bursting resistant ultra-high performance concrete of Examples 1-11 and Comparative Examples 1-2 were made into concrete specimens. The specimens were placed in a high temperature furnace and heated to 350°C at 5°C / min. The temperature was kept constant for 2 hours. The appearance of the specimens was observed. The observation results are shown in Table 4.

[0160] (5) Mass loss rate test: After the above high temperature burst test, the mass loss rate of the specimen before and after the test is calculated. The calculation formula is: mass loss rate = (mass before test - mass after test) / mass before test * 100%. The calculation results are shown in Table 4.

[0161] (6) Residual compressive strength test: After the above high temperature burst test was completed, the specimens of Examples 1-11 and Comparative Examples 1-2 were cooled and their compressive strength was tested. The test results are shown in Table 4.

[0162] Table 4:

[0163]

[0164] As can be seen from Example 1 and Table 4, the concrete prepared in Example 1 has high compressive strength, flexural strength and residual compressive strength, and low drying shrinkage and mass loss rate. It also does not crack or peel at 350°C.

[0165] Compared to Example 1, Comparative Example 1 replaced soybean protein fiber with an equal amount of polypropylene fiber, and Comparative Example 2 replaced soybean protein fiber with an equal amount of porous active aggregate. As shown in Table 4, the compressive strength, flexural strength, and drying shrinkage of the concrete in Example 1 and Comparative Example 1 are comparable, indicating that the mechanical properties of the concrete made with protein fiber in Example 1 meet the standards.

[0166] Furthermore, as shown in Table 4, Comparative Example 1 experienced localized cracking and spalling at 350℃, and its mass loss rate after the cracking test was significantly higher than that of Example 1, while its residual compressive strength was significantly lower than that of Example 1. Comparative Example 2 experienced severe cracking, and its mass loss rate was much higher than that of Example 1, while its residual compressive strength was much lower than that of Example 1. This indicates that the concrete prepared using protein fibers in this invention has excellent mechanical properties and can achieve resistance to high-temperature cracking.

[0167] Compared to Example 1, the calcium-containing cementitious material in Example 2 includes 500 kg / m³ of cement. 3 250kg / m³ of ultrafine mineral admixture 3 As shown in Table 4, the compressive strength, flexural strength, mass loss rate, drying shrinkage rate and residual compressive strength of the concrete in Example 2 are comparable to those in Example 1, and there is no cracking or spalling even at a high temperature of 350℃.

[0168] Compared to Example 1, the content of each component in the raw materials of Examples 3-4 represents the lower and upper limits of the range set by this invention, respectively. As shown in Table 4, the compressive strength, flexural strength, mass loss rate, drying shrinkage rate, and residual compressive strength of the concrete in Examples 3-4 are comparable to those of Example 1, and no cracking or spalling occurred at 350°C. This indicates that by limiting the content of each component in the raw materials within the range of this invention, the prepared concrete exhibits excellent mechanical properties and can resist high-temperature cracking.

[0169] Compared to Example 1, Example 5 replaced soybean protein fiber with an equal amount of wheat protein fiber, Example 6 replaced soybean protein fiber with an equal amount of corn protein fiber, and Example 7 replaced soybean protein fiber with an equal amount of silkworm pupa protein fiber. As shown in Table 4, the compressive strength, flexural strength, mass loss rate, drying shrinkage rate, and residual compressive strength of the concrete from Examples 5-7 are comparable to those of Example 1, and no cracking or spalling occurred at 350℃. This indicates that the concrete prepared using the protein fiber specified in this invention exhibits excellent mechanical properties and can resist high-temperature cracking.

[0170] Compared to Example 1, the volumetric content of soybean protein fiber relative to calcium-containing cementitious material in Example 8 is outside the range set by this invention. As shown in Table 4, the compressive strength, flexural strength, and residual compressive strength of Example 8 are significantly lower than those of Example 1, while the drying shrinkage rate and mass loss rate are significantly higher. Although no bursting occurs at high temperatures, fine cracks appear. This indicates that limiting the volumetric content of soybean protein fiber relative to calcium-containing cementitious material to the range set by this invention results in concrete with superior mechanical properties and resistance to high-temperature bursting.

[0171] Compared to Example 1, Example 9 replaced the porous active aggregate with an equal amount of quartz sand, and Example 11 replaced the porous active aggregate with an equal amount of waste ceramsite. Table 4 shows that, compared to Example 1, although the compressive strength and flexural strength of Example 9 were improved, and it did not crack, its drying shrinkage rate was significantly higher than that of Example 1, and its residual compressive strength after cracking was significantly lower and its mass loss rate was significantly higher than that of Example 1. The compressive strength, flexural strength, and residual compressive strength of Example 11 were all significantly lower than those of Example 1, while its drying shrinkage rate and mass loss rate were significantly higher. This indicates that the concrete prepared by combining porous active aggregate and protein fiber has superior mechanical properties and resistance to high-temperature cracking.

[0172] Compared to Example 1, Example 10 did not soak the porous reactive aggregate in water; it was directly added to the mixing process. As shown in Table 4, the compressive strength, flexural strength, and residual compressive strength of Example 10 were significantly lower than those of Example 1, while the drying shrinkage rate and mass loss rate were significantly higher. Although no bursting occurred at high temperatures, fine cracks appeared. This indicates that concrete prepared from porous reactive aggregate that has undergone water soaking treatment exhibits superior mechanical properties and resistance to high-temperature bursting.

[0173] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A maintenance composition, characterized in that: It includes protein fibers, which undergo thermal denaturation and decomposition within a temperature range of 150-300°C.

2. The maintenance composition according to claim 1, characterized in that: The protein fibers have a weight-average molecular weight of 30-50 kDa, a fiber length of 6-12 mm, a linear density of 1.0-2.0 dtex, and a protein content of ≥80%; and / or, The protein fiber is at least one selected from soybean protein fiber, corn protein fiber, wheat protein fiber, and silkworm pupa protein fiber; and / or, It also includes porous active aggregates, wherein the 24-hour water absorption rate of the porous active aggregates is ≥15%, and the instantaneous water release rate in the high-temperature zone is more than 10 times that in the room-temperature zone, wherein the temperature of the high-temperature zone is 200-600℃, and the temperature of the room-temperature zone is 20-60℃; and / or, It also includes water-reducing agents.

3. The maintenance composition according to claim 2, characterized in that: The porous active aggregate has a particle size range of 0.15-1.18 mm; and / or, The porous active aggregate includes macropores, wherein the pore diameter d1 of the macropores satisfies 50nm < d1 ≤ 500nm; and / or, The porous active aggregate also includes mesopores, wherein the pore size d2 of the mesopores satisfies 2nm≤d2≤50nm.

4. The maintenance composition according to claim 2 or 3, characterized in that: The porous active aggregate is obtained by calcining and activating ceramsite at 500-800℃.

5. A high-performance concrete resistant to high-temperature cracking, characterized in that: It includes concrete matrix materials and the curing composition according to any one of claims 1-4.

6. The high-temperature resistant, high-performance concrete according to claim 5, characterized in that: The concrete matrix material includes calcium-containing cementitious material and aggregate, and the protein fibers are oriented in the calcium-containing cementitious material with an orientation degree of 60%-80%.

7. The high-temperature crack-resistant ultra-high performance concrete according to claim 5 or 6, characterized in that, The components include the following parts by mass: The composition comprises 700-900 parts calcium-containing cementitious material, 80-200 parts porous active aggregate, 800-1000 parts aggregate, protein fiber, water-reducing agent, and water; wherein the volume fraction of the protein fiber relative to the calcium-containing cementitious material is 0.3-1.0%, and the volume fraction of the water-reducing agent relative to the total mass of the calcium-containing cementitious material is 1.8-3.0%; the mass ratio of water to the calcium-containing cementitious material is 0.16-0.20; and / or, The calcium-containing cementitious material includes silicate cement and silica fume, wherein the silica fume accounts for 15-25% by mass, and the remainder is silicate cement.

8. A method for preparing high-temperature resistant ultra-high performance concrete as described in any one of claims 5-7, characterized in that, Includes the following steps: The curing composition and the concrete matrix material are mixed to obtain high-temperature crack-resistant ultra-high performance concrete.

9. The preparation method according to claim 8, characterized in that, The mixing process includes the following steps: Calcium-containing cementitious materials, aggregates, and water-saturated porous active aggregates are mixed and stirred at a frequency of 30-50Hz for 30-60 seconds; then, the water and water-reducing agent are added, and the mixture is stirred at a frequency of ≥50Hz for 2-3 minutes to form a paste; finally, the protein fibers are added, and the mixture is stirred at a frequency of 30-50Hz for 2-4 minutes to obtain high-temperature crack-resistant ultra-high-performance concrete; and / or... The protein fibers are first pre-dispersed and then mixed. The pre-dispersion process includes the following steps: the calcium-containing gelling material includes a first group of materials and a second group of materials. The protein fibers are pre-mixed with the first group of materials. The mass ratio of the first group of materials to the protein fibers is 10%-20%. The second group of materials is directly involved in the mixing process.

10. The preparation method according to claim 9, characterized in that: The water-saturated porous active aggregate is obtained by water soaking pretreatment, which includes the following steps: soaking the porous active aggregate in water for ≥24 hours, and draining off the excess water until it is saturated and surface-dry.

11. A concrete specimen, characterized in that: Including the high-temperature crack-resistant ultra-high performance concrete as described in any one of claims 5-7.

12. A method for casting concrete specimens, characterized in that: The method includes the step of pouring using the high-temperature crack-resistant ultra-high performance concrete as described in any one of claims 5-7.